CONTENT OF MACRO- AND MICROELEMENTS IN THE MILK OF CROATIAN COLDBLOOD MARES DURING LACTATION - Nina Bilandžić; Marija Sedak; Maja Ðokić; Ivana Varenina; Božica Solomun Kolanović; Ðurđica Božić; Ana Končurat (Slovenian Veterinary Research, 2015)
The concentrations of macro- and microelements in the milk of Croatian Coldblood mares were determined throughout the lactation phases by inductively coupled plasma-optical emission spectrometry. Element contents during days 10–180 of lactation were in the ranges (mg/kg): Ca 585–772, K 547–687, Na 131–165, Mg 56.8–71.0, Cu 0.085–0.14, Fe 0.013–0.41, Zn 1.86–2.15, Se 0.003–0.029. Variation trends for elements were found throughout the lactation stages. However, significantly higher Fe concentrations were found on days 10 and 40 of lactation than on day 60 (p < 0.05, both). There were no statistically significant differences between concentrations of other elements during lactation. Moderate correlations were found between the elements: Ca: K, Mg, Se; Mg: K, Cu; Se: Cu, Fe. The element concentrations in horse milk, with the exception of Ca and Cu, fell within the ranges previously reported for different breeds of dairy horses. Cu and Fe contents were lower, while the Zn content was similar to those obtained in different dairy horse breeds. Concentrations of elements obtained in horse milk were lower in comparison to cow and goat milk. Generally, levels of Ca and Mg were higher, Na and K were similar, but Cu, Fe and Zn were lower than those in human milk.